On the Development of the Mental Number Line: More, Less, or Never Holistic With Increasing Age? - Nuerk, Hans-Christoph; Kaufmann, Liane (Developmental Psychology, 2004)
Magnitude is assumed to be represented along a holistic mental number line in adults. However, the authors recently observed a unit-decade compatibility effect for 2-digit numbers that is inconsistent with this “holisticness” assumption (H.-C. Nuerk, U. Weger, & K. Willmes, 2001). This study used the compatibility effect to examine whether the mental number line representation of magnitude changes toward greater or less holisticness in children from Grades 2-5. The results indicate that decades and units of 2-digit numbers are processed separately rather than holistically from Grade 2 on. However, this separate processing seems to develop from a more sequential (left-to-right) to a more parallel processing mode. Moreover, children may use different strategies depending on task demands. The results are interpreted in the framework of Siegler's overlapping waves model. Reprinted by permission of the publisher.